2004
DOI: 10.1111/j.1440-1827.2004.01754.x
|View full text |Cite
|
Sign up to set email alerts
|

Decreased expression of aquaporin‐5 in bleomycin‐induced lung fibrosis in the mouse

Abstract: The expression of aquaporin-5, the major water channel expressed in alveolar, tracheal, and upper bronchial epithelium, is significantly down-regulated during acute lung injury. In the present study, the expression of aquaporin-5 in two different mouse models of lung fibrosis was evaluated. Lung fibrosis was induced by intratracheal and by subcutaneous infusion of bleomycin. The expression of aquaporin-5 was investigated by immunohistochemical studies and by polymerase chain reaction. There were many cells wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
46
0
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 46 publications
(52 citation statements)
references
References 28 publications
5
46
0
1
Order By: Relevance
“…3 similar finding for aquaporin-5 expression. 34 Thus, in contrast to the nonpulmonary diseases studied in which RAGE expression is elevated in disease tissues, 9,10 we found that pulmonary expression of mRAGE and sRAGE is significantly decreased in two models of pulmonary fibrosis and that this depletion is an early event after injury.…”
Section: Pulmonary Mrage and Srage Are Down-regulated After Asbestos mentioning
confidence: 60%
“…3 similar finding for aquaporin-5 expression. 34 Thus, in contrast to the nonpulmonary diseases studied in which RAGE expression is elevated in disease tissues, 9,10 we found that pulmonary expression of mRAGE and sRAGE is significantly decreased in two models of pulmonary fibrosis and that this depletion is an early event after injury.…”
Section: Pulmonary Mrage and Srage Are Down-regulated After Asbestos mentioning
confidence: 60%
“…Cigarette smoke impairs the proteins, ZO-1, ZO-2, and E-cadherin in human bronchial epithelial cells, thus resulting in altered permeability of the epithelial barrier and, potentially, mesenchymal differentiation of epithelial cells (49,69). Thoracic radiation and bleomycin-induced lung injury can also decrease E-cadherin and aquaporin-5 expression in AECs, increasing plasma/water permeability into alveolar spaces (2,9). Immunohistochemistry of lung tissue in aquaporin-5 knockout mice demonstrated fibrosis with increased deposition of type I collagen in alveolar walls (9).…”
Section: R Rmentioning
confidence: 99%
“…Thoracic radiation and bleomycin-induced lung injury can also decrease E-cadherin and aquaporin-5 expression in AECs, increasing plasma/water permeability into alveolar spaces (2,9). Immunohistochemistry of lung tissue in aquaporin-5 knockout mice demonstrated fibrosis with increased deposition of type I collagen in alveolar walls (9). Although these changes in permeability and increased alveolar fluid accumulation are typically associated with acute lung injury, persistent injury to the epithelial barrier may lead to a cascade of reactions with release of soluble factors that promote myofibroblast differentiation and ECM deposition.…”
Section: R Rmentioning
confidence: 99%
“…Immunohistochemical staining of collagen type I and fibrin was then performed by treating the samples with rabbit anti-mouse collagen I antibody (Bethyl Laboratories, Montgomery, TX) or rabbit anti-fibrin(oge)n (DAKO, Glostrup, Denmark) antibody and using the Vectastain ABC kit (Vector Laboratories, Burlingame, CA) as described. 17,18 The samples were then treated with biotin-labeled rabbit anti-mouse IgG, peroxidase-labeled streptavidin, and peroxidase substrate by using the Catalyzed Signal Amplification System from DAKO (Kyoto, Japan). The degree of collagen and fibrin deposition in five areas per lung sample was scored using computer software (WinRoof; Mitani Corp., Fukui, Japan).…”
Section: Immunohistochemistrymentioning
confidence: 99%